Kaji Numerik Pengaruh Bio-Based Lubricant Terhadap Ketebalan Lapisan Film Dan Tekanan Hidrodinamik Pada Journal Bearing Menggunakan Finite Difference Method - Rijaluddin Farihd; Dedi Rosa Putra Cupu; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In journal bearings, there is a contact between the shaft and the bearing. The impact that occurs on these contacts is friction which causes wear on the bearing material. This research was conducted to see the effect of bio-based lubricants on the distribution of hydrodynamic pressure and the film thickness on the journal bearings. The numerical assessment was carried out for this study using one of the numerical methods, namely the finite difference method. The finite difference method is a method commonly used to solve the Reynolds equation in which this equation is used to calculate the pressure distribution. The FDM discretization scheme use in this simulation was central-difference because it has a more accurate value approach to the actual value than using other schemes. This research was conducted by varying several parameters with different results. The different types of bio-based lubricants affect the pressure distribution, but not the film thickness which can only be measured by the eccentricity ratio. It was obtained from several bio-based lubricants, namely coconut oil, olive oil, and palm oil that the better lubricant to use is coconut oil because it produces less pressure for other types of lubricants. Keywords : Journal Bearing, Bio-Based, FDM.